A Tale of Two Manuscripts - Pozdnev, Michael (Philologia Classica, 2019)
The post-Renaissance copies of Aristotle’s Poetics were mostly made for scholarly use. The copyists such as Anton Salvini, a Florentine polymath, librarian and professor of Greek, drew on MSS as well as on printed editions in an attempt to establish the text they could use for translation or academic teaching. Still uncertain remains the rationale of the latest known manuscipts — from the Vatopedi monastery on Mt. Athos (ca. mid 18th cent.) and from Bucharest (of the early 19th cent.). Several similarities these copies display suppose common provenance. The Greek diaspora in Bucharest blossomed around 1800 and Romania is linked to Vatopedi by a long tradition of orthodox learning. The MSS in question provide an overall impression of a schoolwork. The Athoan is of supreme quality while the Romanian often resembles an abstract. The first MS was probably written soon after the foundation of the Athonite Academy near Vatopedi. Aristotle’s Poetics is hardly suitable for monastic learning, but Eugenius Bulgaris who was the headmaster of Athonias from 1753 to 1758 introduced ancient texts into its curriculum: from one of his letters we conjecture that Plato and Aristotle were studied there. It is thus reasonable to suppose that the cod. Vatopedius was made in the Athonias for learning purposes. By 1800 the Academy was in decline but they still taught disciplines and read texts introduced by Bulgaris. So, the Bucarestensis could have been written in the same place. Judging by the composition of the codex its maker was nurturing interest in ancient and modern Greek literature.